Gestão do documentos na administração pública estadual de Minas Gerais: um estudo de caso - Rosilene Silva dos Santos (2013)
The study investigated the management of documents in the public administration of the state of Minas Gerais through the "Project developing tools document management: classification plan and temporality table and disposition of records for the final activities of the executive power." Starting in 2007, the project is the result of a partnership between the Secretariat of State for Culture and the State Secretariat for Planning and Management. We sought to identify the actions taken to carry out the project, and kicking a little in the actions of recent years, features that identify the attempt to establish a policy file in the state. Investigated, also, in the process, the methodology of using the standing committee evaluation of records, pointing to aspects such as their training, responsibilities, activities and challenges encountered in the course of realization of the project. Tried to demonstrate through the qualitative approach and descriptive aspects to identify the stages of formulation and implementation of public policy in the state file. It started from the assumption in the literature of the area, that not just a legal basis for the management of documents actually happen. The data collected through documentary analysis, questionnaires and interviews showed that although the state has made progress towards legislation will archive and institutionalization of bodies responsible for monitoring the actions related to public documents and files, issues awareness of managers about the importance of document management, lack of training and capacity building of stakeholders, among others, lead to discontinuity of actions related to document management in Minas Gerais. APM, archival institution of the executive power of the state, carried out the project fulfilling its responsibility to guide the actions of the organs document management. But it was evident that it is necessary to give this organ greater autonomy and participation in decisions relating to management activities documental. We recognize that to continue the actions APM must have, minimally, physical structure, staffing and budget. The commission took great responsibility in project implementation. However, the use of the same methodology requires restructuring. Aspects such as education, training, financial incentives and exclusive dedication are seen as mechanisms to overcome difficulties.